Kualitas Kebahasaan Disertasi Mahasiswa Pascasarjana: Analisis Metafungsi Interpersonal Berdasarkan Pendekatan Linguistik Fungsional Sistemik - Wajdi, Fathullah; R., Mantasiah (Universitas Muhammadiyah Surabaya, 2025)
This study aims to evaluate the linguistic quality of postgraduate dissertations through interpersonal metafunctional analysis based on the Systemic Functional Linguistics and Appraisal Theory approaches. This study uses a descriptive qualitative approach with discourse analysis on three dissertations from Makassar State University. The results of the analysis indicate that students are able to apply mood, modality, and evaluative attitudes fairly well, particularly in maintaining objectivity and consistency in academic style. However, weaknesses were identified in the variation of epistemic modality expressions and evaluative lexical justifications. These findings emphasize the importance of strengthening academic learning based on interpersonal functions to enable students to construct more credible and reflective arguments in scientific texts.